Influence of self-efficacy beliefs on academic writing performance of ESL students / Insani Genam - Genam, Insani (2009)
The study aimed to investigate the influence of writing self-efficacy beliefs on the students' academic writing performance. The study involved a group of 60 technical ESL students at MARA Vocational Institute in Kuching, Sarawak. Out of 60, 25 were female and 35 male students. The sample was chosen based on convenience sampling whereby the group is available to partake in the study. The students' level of proficiency was determined based on their SPM English grades as these students were fresh from Form Five. Out of 60, 28 were considered of high proficiency as they obtained C4 to A2 in their SPM English paper while the other 32 were of low proficiency as they obtained grades below C4 for their English in their SPM. The study employed two main instruments namely, self-constructed Self-efficacy Scale (SES) and Writing Scoring Rubric (WSR). The SES sets of questionnaire were collected upon completion by the participants. The participants' essays were collected at the end of the investigation which spanned over a two-week period, and the essays were scored using WSR. The data on self-efficacy beliefs were analysed using the SPSS Version 16 for descriptive statistics to determine the participants' level of self-efficacy beliefs. The participants' essay scores were analysed using the WSR Rubric to determine their level of writing ability in the forms of percentage score up to maximum of 100%. The SES scores and the essay scores were analysed using the SPSS Version 16 for a two-way Pearson correlation test. The level of significance was established at p < 0.05. The findings indicated that generally the students regardless of gender or proficiency level were aware of the various sub-processes involved in academic writing. Only female writers showed a significant correlation based on Pearson two-way significance test suggesting that the female students were less apprehensive in approaching their writing tasks.